Efektifitas Penggunaan Modul Pembelajaran Terhadap Peningkatan Pengetahuan Siswa Tentang Influensa Like Illness - Ida Djafar; M Mintje Nendissa; Suardi Zurimi (GLOBAL HEALTH SCIENCE, 2021)
Children are a group with a high level of vulnerability especially because they are in the process of growth. Disrupted growth due to disease will affect the degree of health. Growing children are at risk for decreased immune system resulting in children getting sick, especially respiratory diseases, namely Influenza Like Illness which most often affects preschool or school age children. Data from the West Seram Health Office The 10 most common diseases in 2019 (January-July) were occupied by influenza like illnesss with a total of 2,552 cases (male = 1,228 cases; 1,324 women. There are 1514 children (0-14 years old). The use of modules is one method that can develop positive knowledge and attitudes to health. The purpose of this study is to determine the effectiveness of the use of learning modules to increase students' knowledge about Influenza Like Illness. Method: This quantitative research uses a learning module with a quasi-experimental design with pre and post test One Group design. The population is all students of the Patinia Public Elementary School, Patinia Hamlet, Kawah Village, West Seram District, which is the working area of Puskesmas piru, West Seram Regency with a purposive sampling technique. as many as 20 students from perwa kilan each of class IV, V and class VI, so that the number of research subjects is 60 students. Processing data with the N-Gain Score experimental class with paired sample t test. Result: shows that the mean value (mean) of N-Gain percent is 57.8553. Based on the category table of the interpretation of the effectiveness of the N-Gain value (%) above, it can be concluded that the use of learning modules is effective enough to increase students' knowledge about Influenza Like Illness. Conclusions: The use of modules in learning about Influenza Like Illness is very effective in increasing the knowledge of elementary school studentsKeywords: influensa like illness; module